Large Enterolith Complicating a Meckel Diverticulum Causing Obstructive Ileus in an Adolescent Male Patient - Constantinos Nastos; Dimitrios Giannoulopoulos; Ioannis Georgopoulos; Christos Salakos; Dionysios Dellaportas; Ioannis Papaconstantinou; Theodosios Theodosopoulos; Georgios Polymeneas (Case Reports in Surgery)
We present a unique case of a 16-year-old male patient who was eventually diagnosed with a large enterolith arising from a Meckel’s diverticulum. The enterolith had caused intermittent intestinal symptoms for three years before resulting in small bowel obstruction requiring surgical intervention. Meckel’s enterolith ileus is very rare with only few cases described in the literature. To our knowledge, this is only the second case of Meckel’s enterolith which had caused intermittent symptoms over a period of time, before resulting in ileus, and the first case where the intermittent symptoms lasted several years before bowel obstruction. The patient had been evaluated with colonoscopy, computerized tomography (CT), and magnetic resonance imaging enterography (MRIE); a calcified pelvic mass had been found, but no further diagnosis other than calcification was established. The patient presented at our emergency department, with symptoms of obstructive ileus and underwent exploratory laparotomy, where a large enterolith arising from a Meckel’s diverticulum (MD) was identified, causing the obstruction. A successful partial enterectomy, enterolith removal, and primary end-to-end anastomosis took place; the patient was permanently relieved from his long-standing symptoms. Consequently, complications of Meckel’s diverticulum and enterolithiasis have to be included in the differential diagnosis of abdominal complaints.